Research in organizational change and development. Vol. 29 - Shani, Abraham B.; Noumair, Debra A. (Research in organizational change and development ;, 2021)
Volume 29 of Research in Organizational Change and Development includes ten contributions from colleagues around the globe with powerful insights and potentially relevant impact for researching and practicing organization change and development during and post the pandemic. The emerging people analytics subfield and organization development perspectives are brought together to present an integrated framework that can guide future theoretical development and practice. Bourdieu's concept of social position in the form of "habitus oriented approach" expands our understanding of human behavior. Lewin's original view of political labs is advanced to examine the emerging phenomenon of labs as mechanisms for organization change and development. The alignment challenges of strategy and digital technology in government organizations is examined via the use of collaborative inquiry. The essence and context of collaboration in teams is investigated in the emerging new workplace. The current state of organizational DEI practice is examined and a new framework for diagnosing and addressing small-scale diversity-related challenges is introduced. Digital transformation suggests the need for a new STS platform with new guiding design principles. The establishment of a collaborative community generated insights into the challenges faced by healthcare organizations. Action research supported new cooperation and partnership between universities and external organizations. In the new "Reflection" feature, the author compares organization development (OD) and change management (CM) across eight concepts that are relevant to both OD and CM.